2008
DOI: 10.1121/1.4783033
|View full text |Cite
|
Sign up to set email alerts
|

Psychoacoustic measures of stop production in Cantonese, Greek, English, Japanese, and Korean.

Abstract: Spectral analyses of stop bursts have revealed that the place of articulation can be predicted based on both invariant and time-varying cues present within the acoustic signal (e.g., Stevens and Blumstein, 1978; Forrest et al., 1988). While prior studies have had some success in uncovering such cues for American English, it is not clear whether these parameters are equally pertinent in stoping consonant classification in other languages. Furthermore, one of the main limitations of a linear acoustic analysis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Multiple regressions predicting the average ratings for the inexperienced and experienced listeners' ratings from the peak ERB, compactness, and peak loudness of the stop bursts were conducted separately for front- and back-vowel contexts, as work by Arbisi-Kelm et al (2008) showed that different sets of psychoacoustic measures discriminated between /t/ and /k/ in different vowel contexts. The correlations between the acoustic measures and responses was so low that the analyses were not meaningful and are hence not reported here.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple regressions predicting the average ratings for the inexperienced and experienced listeners' ratings from the peak ERB, compactness, and peak loudness of the stop bursts were conducted separately for front- and back-vowel contexts, as work by Arbisi-Kelm et al (2008) showed that different sets of psychoacoustic measures discriminated between /t/ and /k/ in different vowel contexts. The correlations between the acoustic measures and responses was so low that the analyses were not meaningful and are hence not reported here.…”
Section: Resultsmentioning
confidence: 99%
“…The stimuli were analyzed using a set of psychoacoustic measures, as described in Arbisi-Kelm, Beckman, Kong, and Edwards (2008), Arbisi-Kelm et al (2010), and Munson et al (2010). Briefly, these are measures of the spectra of the stop bursts and the intervals of frication that are based on models of human hearing, rather than on linear measures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Greek speakers, for example, rated the English velar tokens as more-front than the English-speaking listeners did. This cross-language asymmetry indicates that this perception is mediated by language-specificity in the way that phonological contrasts are expressed, a topic that we explore further in Arbisi-Kelm, Beckman, Kong, and Edwards (2008).…”
Section: Covert Contrast Is Everywherementioning
confidence: 93%
“…Additionally, measures of duration and of the second-formant frequency at vowel onset (in ERB) are reported in Table II. A defence of the psychophysical measures, as well as an illustration of their benefit over traditional linear measures, can be found in Arbisi-Kelm, Beckman, Kong, and Edwards (2008).…”
Section: Methodsmentioning
confidence: 99%